Ending AIDS as a public health threat by 2030: Time to reset targets for 2025. - Paul R De Lay; Adèle Benzaken; Quarraisha Abdool Karim; Sani Aliyu; Carolyn Amole; George Ayala; Kalipso Chalkidou; Judy Chang; Michaela Clayton; Aleny Couto; Carl Dieffenbach; Mark Dybul; et al. (PLoS Medicine)
Paul De Lay and co-authors introduce a Collection on the design of targets for ending the AIDS epidemic.